DAMPAK PENGGUNAAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN GAYA BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Rumondang Bulan BR Rambe; Firman; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research was conducted with the aim of obtaining data and information about "How is the Impact of the Contextual Teaching and Learning (CTL) Approach and Learning Styles on Students' Mathematics Learning Outcomes in Elementary Schools?". This study used an experimental approach with a 2x2 factorial by level design. This research was conducted at SD Negeri 06 Piai Tangah. The research subjects were VA and VB class students, totaling 60 students. When the research was conducted in the odd semester of the 2022/2023 academic year. The sampling technique used is the Random Sampling technique by taking 2 classes at random. The results of the study were analyzed using a two-way analysis of variance technique (ANAVA 2 x 2). Prior to ANAVA, a requirements analysis test was carried out, which included the normality test with the Lilifors test and the calculation results of the advanced test using the Tuckey test. The results of the study show that the application of the Contextual Teaching and Learning (CTL) and Learning Style approaches can improve student learning outcomes in elementary schools.